Toxicological Risk Assessment of Chemicals: A Practical Guide - Nielsen, Elsa (CRC Press, 2009)
Unlike many existing books on toxicology that cover either toxicity of a particular substance or toxicity of chemicals on particular organ systems, Toxicological Risk Assessment of Chemicals: A Practical Guide lays out the principle activities of conducting a toxicological risk assessment, including international approaches and methods for the risk assessment of chemical substances. It illustrates each step in the process: hazard identification, a dose response assessment, and exposure assessment. The book also summarizes the basic concepts of interaction of chemicals in mixtures and discusses various approaches to testing such mixtures.